Optical properties of metal-composite-based thin films - Gozhenko, V.V.; Grechko, L.G.; Goncharuk, Yu.S.; Ogenko, V.M. (Поверхность, 2002)
In the first part of this work we study the effect of a semi-infinite matrix dispersed system (MDS) on the external electromagnetic radiation in the electrostatic approximation. With the help of our previous technique, we obtain general expressions for the multipole expansion coefficients of the electric potential for a sphere accounting for the interaction between ambient particles and the substrate. The polarizability tensor and resonant frequencies of a single sphere show anisotropy due to the influence of a substrate. In the second part electrodynamical properties of thin percolating layers manufactured on the basis of the MDS are considered. Transition from 3-D to 2-D behavior, which is observed near the percolation threshold and shows itself as changing of some parameters (in comparison with those for 3-D percolating system) like the values of percolation threshold, critical indices of conductivity and permittivity, were studied.